Asset-based community sport development: putting community first. Issue 1 (4th March 2021) - Bates, Dan; Hylton, Kevin
ABSTRACT: Rationale: Community sport practitioners often face the dual challenge of creating and sustaining inclusive provision, whilst also aspiring to demonstrate the wider social impacts of their interventions. This enduring challenge has prompted a growing interest in the adoption of "asset-based" approaches as a way to facilitate provision without the resource-intensive commitments of programme delivery. Approach: This article draws upon a case study of asset-based community sport development to reveal an application of this innovative approach. Findings: A community-orientated ethos and participatory processes are identified as key components of an asset-based approach. The findings provide much needed theoretical and practical insight into the actualities and implications of their adoption. Practical implications: The paper concludes that an asset-based approach has the potential to aid practitioners and policymakers in their laudable aspirations of inclusive provision and pursuit of social goals through sport. Research Contribution: This research is the first to examine the use of an asset-based approach in community sport provision, providing insights into a particular "family of mechanisms" crucial to understanding the potential of Community Sport Development.